The environmental fate of graphene oxide in aquatic environment-Complete mitigation of its acute toxicity to planktonic and benthic crustaceans by algae - Malina, Tomáš; Maršálková, Eliška; Holá, Kateřina; Zbořil, Radek; Maršálek, Blahoslav (Journal of hazardous materials, 2020)
Graphene oxide (GO) as the most studied hydrophilic graphene derivative can be deployed in a broad spectrum of environmental technologies opening the issue of its ecotoxicity. Nevertheless, the information about its behavior in complex aquatic environment is still not sufficient. Here, we studied the interaction of three differently oxidized GO systems with planktonic and benthic crustaceans. By standard toxicity tests, we observed the importance of feeding strategy as well as the surface oxidation of GO with respect to GO's ecotoxicity. However, to gain a clearer insight into GO's environmental fate, we introduced a pre-treatment with algae as the most common source of food for crustaceans. Such an adjustment mimicking the conditions in real aquatic ecosystems resulted in complete mitigation of acute toxicity of GOs to all organisms and, more importantly, to the eradication of oxidative stress caused by GOs. We argue, that the pre-exposition of food is a crucial factor in GO's overall environmental fate, even though this fact has been completely neglected in recent studies. These experiments proved that GO is not a hazardous material in complex aquatic environments because its acute toxicity can be successfully mitigated through the interaction with algae even at very high concentrations (25 mg/L).
Keywords: grafit; plankton; Plankton; Water Pollutants, Chemical; testy toxicity; zvířata; ekosystém; Ecosystem; Toxicity Tests; chemické látky znečišťující vodu; Graphite; Animals